The Relationship Of Mobilization To Episiotomy Wound Healing In Post Partum Mothers At Palembang Ar-Rasyid Hospital - Rosdiana, Meta; Putinah, Putinah (Universitas Islam Lamongan, 2020)
Early mobilization as a prominent factor in accelerated the recovery of postoperative maternal body functions and to prevent post-surgical complications. This study aims to determine the relationship of mobilization to episiotomy wound healing in post partum mothers. This research is a quantitative descriptive study with cross sectional approach. The samples were 30 respondents with all post partum mothers treated at Ar-Rasyid Hospital Palembang. The results of the analysis found of respondents mobilized were 17 people (56.7%) and respondents experienced rapid episiotomy wound healing were 22 people (73.3%). There is a relationship between mobilization and episiotomy wound healing in post partum mothers at the Ar-Rasyid Hospital in Palembang in 2019 (Ï = 0.011).